Antipatterns : identification, refactoring, and management. - Laplante, Phillip A., ....-; Neill, Colin J., ....- (New York : Auerbach Publications, 2006)
AntiPatterns: Identification, Refactoring, and Management catalogs 48 bad management practices and environments common to software development, IT, and other organizations. The authors cover antipatterns of management, along with environmental/cultural antipatterns and personality antipatterns/phenotypes. Through the classification of these harmful practices, you will be able to identify problems in your own work environment, and take action to correct them. Following introductory material describing management theory and how humans behave individually and in groups, the text provides the catalog of management and environmental antipatterns. The book then offers general advice on overcoming bad practices through successful interaction with clients, customers, peers, supervisors, and subordinates.